2010
DOI: 10.1002/ppul.21269
|View full text |Cite
|
Sign up to set email alerts
|

Community‐acquired Staphylococcus aureus pneumonia among hospitalized children in Hawaii

Abstract: Younger Pacific Islander/Native Hawaiian children were affected disproportionately and had MRSA infection more frequently. MRSA infected patients appeared to have severe disease with frequent chest tube placement, intubation, and fatality. Overall, both MRSA and MSSA pneumonia resulted in prolonged hospitalization, multiple complications, and significant healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
1
13
0
1
Order By: Relevance
“… 40 Pneumonia caused by MRSA is associated with a higher rate of complications such as pleural effusion, pleural thickening, increased requirement for tube placement, pneumatoceles and high mortality rates with no differences in demographic data, days with fever, tachypnea, hypoxia, and length of hospital stay. 41 , 42 In this study, a higher frequency of complicated pneumonia was found [MRSA 13 (57%) vs. MSSA 5 (24%)]. Some studies have already described a particularly higher frequency of lung abscess and necrotizing pneumonia.…”
Section: Discussionsupporting
confidence: 45%
“… 40 Pneumonia caused by MRSA is associated with a higher rate of complications such as pleural effusion, pleural thickening, increased requirement for tube placement, pneumatoceles and high mortality rates with no differences in demographic data, days with fever, tachypnea, hypoxia, and length of hospital stay. 41 , 42 In this study, a higher frequency of complicated pneumonia was found [MRSA 13 (57%) vs. MSSA 5 (24%)]. Some studies have already described a particularly higher frequency of lung abscess and necrotizing pneumonia.…”
Section: Discussionsupporting
confidence: 45%
“…After S. pneumoniae , S. aureus was the next most common pathogen, which was identified by culture in 17 pleural fluid and 2 blood specimens (12 MSSA, 7 MRSA) and by PCR in 13 specimens (Table 2). The occurrence of MRSA as a cause of community-acquired pneumonia and empyema is of particular concern because it is associated with more severe disease and a higher rate of complications than MSSA ( 9 ). …”
Section: Discussionmentioning
confidence: 99%
“…Other important causes, which are becoming increasingly frequent in several countries, are methicillin-sensitive Staphylococcus aureus (MSSA) ( 2 , 7 , 8 ) and methicillin-resistant S. aureus (MRSA). The latter is particularly problematic in indigenous communities ( 9 ). Other commonly identified organisms include S. pyogenes, Haemophilus influenzae , Mycoplasma pneumoniae , Pseudomonas aeruginosa , and other Streptococcus spp ( 10 ).…”
mentioning
confidence: 99%
“…Previous studies have shown a higher prevalence of MRSA infections in the State of Hawaiʻi compared to the national average [ 18 , 19 ]. Native Hawaiians, Pacific Islanders, and children are disproportionately affected and have a higher infection rate of community-acquired MRSA infections [ 13 , 20 , 21 ]. A steady increase in the proportion of MRSA, compared to MSSA infections, has been reported in inpatient and outpatient clinics, jails, and nursing homes in Hawaiʻi [ 13 , 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%